Base-Modified Nucleosides: Etheno Derivatives - Jahnz-Wechmann, Zofia; Framski, Grzegorz R.; Januszczyk, Piotr A.; Boryski, Jerzy (Frontiers in Chemistry, 2016)
This review presents synthesis and chemistry of nucleoside analogs, possessing an additional fused, heterocyclic ring of the “etheno” type, such as 1,N6-ethenoadenosine, 1,N4-ethenocytidine, 1,N2-ethenoguanosine, and other related derivatives. Formation of ethenonucleosides, in the presence of α-halocarbonyl reagents and their mechanism, stability and degradation, reactions of substitution and transglycosylation, as well as their application in the nucleoside synthesis, have been described. Some of the discussed compounds may be applied as chemotherapeutic agents in antiviral and anticancer treatment, acting as pro-nucleosides of already known, biologically active nucleoside analogs..